2019
DOI: 10.1186/s12940-019-0453-y
|View full text |Cite
|
Sign up to set email alerts
|

The Ramazzini Institute 13-week pilot study glyphosate-based herbicides administered at human-equivalent dose to Sprague Dawley rats: effects on development and endocrine system

Abstract: BackgroundGlyphosate-based herbicides (GBHs) are broad-spectrum herbicides that act on the shikimate pathway in bacteria, fungi, and plants. The possible effects of GBHs on human health are the subject of an intense public debate for both its potential carcinogenic and non-carcinogenic effects, including potential effects on the endocrine system The present pilot study examine whether exposure to GBHs at the dose of glyphosate considered to be “safe” (the US Acceptable Daily Intake - ADI - of 1.75 mg/kg bw/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 51 publications
(58 reference statements)
5
49
0
2
Order By: Relevance
“…It remains to be determined whether Glyphosate or Roundup alter the peripheral and central actions of gonadal and adrenal hormones in the mother. Previous research on human cell lines, human breast cancer cells and rodents has shown that glyphosate‐based herbicides in formulation can disrupt steroid secretion, oestrogen receptors and aromatase activity, albeit the exact mechanisms remain to be determined. The physiological and behavioural effects of glyphosate observed in the present study could be linked to endocrine disruption, and future work will aim to investigate this possibility.…”
Section: Future Directionsmentioning
confidence: 99%
“…It remains to be determined whether Glyphosate or Roundup alter the peripheral and central actions of gonadal and adrenal hormones in the mother. Previous research on human cell lines, human breast cancer cells and rodents has shown that glyphosate‐based herbicides in formulation can disrupt steroid secretion, oestrogen receptors and aromatase activity, albeit the exact mechanisms remain to be determined. The physiological and behavioural effects of glyphosate observed in the present study could be linked to endocrine disruption, and future work will aim to investigate this possibility.…”
Section: Future Directionsmentioning
confidence: 99%
“…Many studies have reported that commercially formulated pesticide products are more toxic than their active ingredient. This has been shown multiple times for glyphosate-based herbicides (Adam et al 1997;Manservisi et al 2019;Mesnage et al 2013), and also for other classes of pesticides such as insecticides or fungicides (Mesnage et al 2014). This difference in toxic effects is generally due to the toxicity of surfactants and other compounds that constitute the adjuvant mixture in commercial pesticide formulations , although it cannot be excluded that these surfactants can also potentiate glyphosate penetration in tissues (Anadón et al 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Newly published reports are demonstrating previously unrecognized health impacts of glyphosate exposure, including a meta analysis of epidemiologic studies showing a link between glyphosate based herbicide expsoure and increased risk of Non-Hodgkin Lymphoma [11] and a long-term low dose toxicologic assessment that showed glyphosate and Roundup had developmental and endocrinological impacts in sprague dawley rats [12].…”
Section: Discussionmentioning
confidence: 99%